The efficacy and therapy management of nab-paclitaxel in the real-world setting for patients with advanced breast cancer - the SERAPHINA study - Schneeweiss, Andreas; Fasching, Peter A.; Thill, Marc; van Mackelenbergh, Marion; Marmé, Frederik; Tesch, Hans; Fehm, Tanja N.; Park-Simon, Tjoung-Won; Häberle, Lothar; Uhrig, Sabrina; Tome, Oliver; Spall, Thomas; et al. (Journal of cancer research and clinical oncology, 2025)
Chemotherapies are still widely used in advanced breast cancer, specifically in patients with HER2-negative disease. This non-interventional real-world study assessed the utilization of nab-paclitaxel in a broad patient population with advanced breast cancer.
Gesehen am 12.09.2025